2014
DOI: 10.1073/pnas.1401065111
|View full text |Cite
|
Sign up to set email alerts
|

Direct single-molecule observation of calcium-dependent misfolding in human neuronal calcium sensor-1

Abstract: Neurodegenerative disorders are strongly linked to protein misfolding, and crucial to their explication is a detailed understanding of the underlying structural rearrangements and pathways that govern the formation of misfolded states. Here we use singlemolecule optical tweezers to monitor misfolding reactions of the human neuronal calcium sensor-1, a multispecific EF-hand protein involved in neurotransmitter release and linked to severe neurological diseases. We directly observed two misfolding trajectories l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
53
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 62 publications
(92 reference statements)
1
53
0
Order By: Relevance
“…These experiments revealed a sequential folding process where the C-domain first collapses into a partially folded structure and then undergoes a minor rearrangement to transit into its native conformation before the folding of the N-domain (11). We also showed that NCS-1 could become transiently kinetically trapped in two distinct misfolded states where pathologically high calcium concentrations increased the lifetimes of the misfolded structures (21). Although significant information is available on the structure, stability, and folding of NCS-1 in its Ca 2þ -bound state, little is still known about its structural and dynamical properties in the absence of Ca 2þ .…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…These experiments revealed a sequential folding process where the C-domain first collapses into a partially folded structure and then undergoes a minor rearrangement to transit into its native conformation before the folding of the N-domain (11). We also showed that NCS-1 could become transiently kinetically trapped in two distinct misfolded states where pathologically high calcium concentrations increased the lifetimes of the misfolded structures (21). Although significant information is available on the structure, stability, and folding of NCS-1 in its Ca 2þ -bound state, little is still known about its structural and dynamical properties in the absence of Ca 2þ .…”
Section: Introductionmentioning
confidence: 76%
“…Likewise, the folding mechanism of NCS-1 in the presence of Ca 2þ has been studied extensively using both traditional ensemble methods (4,19) and single-molecule experiments with optical tweezers (11,21). Through mechanical manipulation, we have recently characterized the energy landscape of the Ca 2þ -bound state of NCS-1.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review provides details of studies that have employed the Zhurkov-Bell model to extract parameters of the unfolding energy landscape of a protein from experimental data on polyproteins [43]. In addition, since that review, 12 additional studies have used the Zhurkov-Bell model to extract information from force spectroscopy experiments [15,[44][45][46][47][48][49][50][51][52][53][54]. Given the prevalence of the Zhurkov-Bell model in force spectroscopy experiments, it is interesting to examine its application and accuracy in more detail.…”
Section: Introductionmentioning
confidence: 99%
“…Although the in vitro folding of small and mediumsized proteins is relatively well understood (1)(2)(3)(4)(5), very limited information exists about the complete folding process of such large proteins (6). In general, larger proteins often exhibit a multitude of intermediate and aggregation-prone misfolded states (4,7). Recently, it has been shown that in multidomain proteins with homologous domains, cross-repeat intermediates can greatly slow down productive folding (8) but little is known about how size effects influence the folding of very large (>500 residues) nonhomologous multidomain proteins.…”
mentioning
confidence: 99%